Survey and documentation of anthelmintic plants used in traditional medicine system of tribal communities of Udalguri district of Assam, India - Ananta Swargiary, Manita Daimari, Mritunjoy Kumar Roy (Journal of Applied Pharmaceutical Science, 2020)
The present study was aimed to survey and document the anthelmintic medicinal plants traditionally used by the tribal communities of Udalguri district of Assam. The survey was conducted in different villages of the district following a face-to-face interview and a readymade questionnaire. The study found that a total of 75 plant species belonging to 67 genera and 44 plant families were used as deworming agents. The result showed that Andrographis paniculata, Ananas comosus, Hydrocotyle sibthorpioides, and Centella asiatica were the most popular plant species. Acanthaceae family was found to be most common among the traditional healers. The leaves were found to be commonly used plant parts for herbal preparation. Decoction, infusion, and raw preparations were found to be the most commonly used traditional formulation methodologies. The present study could be used to identify the potential anthelmintic plants and in designing new anthelmintic drug having better property and efficacy.
Keywords: Anthelmintic, ethnomedicine, traditional healer, Udalguri, Assam.